2001
DOI: 10.1089/104454701750066875
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Percutaneous Laser Disc Decompression: Preliminary Results of an Ongoing Prospective Outcome Study

Abstract: The sustained nature of the benefit (mean 3.5 years at final follow up) after long-term preoperative symptoms (mean 3.9 years) in 76% patients rules out placebo effect. Benefits occurred independently of the wavelength of laser used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…This is a relatively new surgical technique and is usually coupled with laser application to increase the success rate. [8][9][10][11][12][13][14][15] The Ho:YAG laser is a useful tool for percutaneous endoscopic disc decompression. [8][9][10][11][12][13][14][15][16][17][18][19] The reported success rates of PLDD using a Ho:YAG laser vary from 76% to 94.5%, which is comparable to the traditional open approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a relatively new surgical technique and is usually coupled with laser application to increase the success rate. [8][9][10][11][12][13][14][15] The Ho:YAG laser is a useful tool for percutaneous endoscopic disc decompression. [8][9][10][11][12][13][14][15][16][17][18][19] The reported success rates of PLDD using a Ho:YAG laser vary from 76% to 94.5%, which is comparable to the traditional open approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Laser energy is usually employed to increase the success rate of this procedure. [8][9][10][11][12][13][14][15] Although several investigators have shown satisfactory results with PLDD with a laser, little is known about long-term clinical outcome and prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Tajima et al [5] first described percutaneous cervical discectomy (PCD) in 1989 and since then there have been several reports describing the efficacy using various instruments such as nucleotome, laser and endoscopy [6]. PECD has shown good outcomes with soft disc herniation and cervicogenic headache [7][8][9] associated with lower cervical spine segments and has been reported to be successful as by several authors [10][11][12][13]. However, this technique has a steeper learning curve and vigilant placement of the working channel of endoscope is the most important step of the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Sequestered herniated intervertebral discs, in particular, involve open as well as endoscopic surgery. Following successful results in the treatment of herniated lumbar intervertebral discs in 1990, PLDD was more frequently performed in the region of the cervical spine 15,16 and in the thoracic spine. 17 Severe complications still are reported following this procedure.…”
Section: Introduction H Erniated Cervical Intervertebral Discs and Prmentioning
confidence: 99%
“…17 Severe complications still are reported following this procedure. 16,19 Until now, no experimental basic research has been reported regarding temperature rise and reaction to ablation in intradiscal laser treatment in the region of the cervical spine. The aim of this study was to determine whether application of the presently used clinical parameters for laser treatment in the spine are detrimental to the neurovascular structures and whether the technical parameters should be further optimized.…”
Section: Introduction H Erniated Cervical Intervertebral Discs and Prmentioning
confidence: 99%